A study of culture and how it affects Sri Lankan organisations - Perera, Ethmadalage Dineeli Nadeesha (2006)
This dissertation presents a study of culture by bifurcating it into two parts: National and Organisational Culture. Through research, a profile of the Sri Lankan National Culture and the Organisational Culture of 3 selected companies is arrived at. Consequently, the research findings are analysed to distinguish if the National Culture of Sri Lanka has had an influence on the Organisational Culture of Sri Lankan companies.